Persembahan Ritual Hindu Yang Sehat Dalam Berkomunikasi Dengan Tuhan - Yupardhi, W. Sayang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Communication of Hindu people in Bali with their God is never forgetting to use offering and it mate- rials as symbols of universe and human being to look after micro and macro cosmos balances. From various rituals, most of them that dedicated to the God were completed with meat of animals slaugh- tered. Unfortunately, most of them were not completed with slaughter certificate from legislator so, it canâ€™t be detected whether the meat is healthy or not. The offerings were made very artistic, beautiful and interesting physically with an expectation that the God vibration could increase healthy soul and communications with the God as what were said by holy men. But, it must be remember that all offerings that dedicate and communicate with the God must be healthy, clean, free of diseases, etc. as well asÂ for human consumption. The animals used in the ritual are no need to be slaughtered (â€œahimsaâ€) due to principle of â€œadwesta sarwa bhutanamâ€, it means no kill any creatures (the Holly Book of Hindu, Bhagawad Gta XII. 13 and 14).